Investigation of biological effects of some Mannich Bases containing Bis-1,2,4- Triazole - Parlak, A E; Celik, S; Karatepe, M; Turkoglu, S; Alayunt, N O; Dastan, S D; Ulas, M; Sandal, S; Tekin, S; Koparir, M (Cellular and Molecular Biology, 2016)
In this study, the effects of Mannich bases containing bis-1,2,4-triazole on the levels of in vivo malondialdehyde (MDA) and antioxidant vitamins (A, E, C) were examined in serum, livers and kidneys of rats. DA and vitamin (A, E, C) levels were determined by high performance liquid chromatography (HPLC). Antioxidant effect was investigated by determining the MDA levels in Saccharomyces cerevisiae cells as in vitro. Furthermore, the antitumor effects of compounds were investigated against MCF-7 human breast cancer cells. Interrelations of results among control and compound groups were evaluated using SPSS statistical software package. As a result, some of the compounds showed effective biological activity when compared to control conditions. The test compounds used in this study may be effective for utilization in the selection and design of model compounds for further studies.